Peningkatan Hasil Belajar IPA dengan Metode Teams Assisted Individualization - Gamar Al Haddar; Ayu Novita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to improve the learning outcomes of science through cooperative learning methods of the Teams Assisted Individualization type. In grade IVA students at SD10 010 Sungai Kukung in the 2018/2019 school year. This type of research is classroom action research with 34 research subjects. Data collection techniques used in this study were Observation, Test and Documentation. This research was conducted in 3 cycles and each cycle consisted of 2 meetings, each cycle consisting of four stages, namely: Planning, Implementation, Observation, and Reflection. The results showed that there was an increase in each cycle with the percentage in cycle I 32.35% then increased in cycle II to 58.82% and increased again in cycle III to 94.11%. Conclusions, while the results of the value of skills and attitude values ​​that include the value of social attitudes and spiritual attitudes also experience an increase in each aspect. Thus the Teams Assisted Individualization Method can improve student learning outcomes in Natural Sciences. Keywords: Teams Assisted Individualization Method, Learning Outcomes